Electricity demand in Singapore : perspectives from household characteristics and weather - Choo, Ying Ning (2015)
This study examines the factors affecting residential electricity demand in Singapore in the short- and long run. It employs monthly data over the period of 2005 – 2013 and the residential demand for electricity is estimated using multivariate framework analysis. A long run residential demand function for electricity consumption, income, price level, household size, ownership of air-conditioner and refrigerator, and mean temperature is found to exist from the results of Johansen maximum likelihood technique. The importance of short run deviations of the variables from long run equilibrium is presented using vector error correction model (VECM) estimation. Results show that short run residential electricity demand in Singapore is affected by income, ownership of air-conditioner and mean temperature. On the other hand, household size, ownership of air-conditioner and refrigerator are found to have significant impact on residential electricity consumption in the long run. In addition, short run fluctuations in electricity demand are attributed to income, price level, ownership of air-conditioner and mean temperature. The empirical evidence suggests that regulation through pricing mechanism is ineffective in affecting the residential electricity demand. Alternatively, continual education on energy conservation and encouraging households to purchase energy-efficient products are advocated to reduce electricity demand.